Differences in long jump takeoff techniques among combined events athletes of various qualifications - Nemtsev, O.; Nemtseva, N.; Shubin, M.; Sorokin, S. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The aim of this study was to compare the kinematic characteristics of the movements made by combined events athletes of different qualifications at support phase in long jump. The long-jump performances of twenty-five combine events athletes had been videotaped at the Southern Federal District of Russia Championship for further 2D video analysis. Was used 240 Hz video camcorder. The kinematic data of the best twelve and the weakest thirteen athletes in long jumps were ?compared. It has been found that more qualified athletes have significantly smaller contact time and significantly larger knee angle at touchdown, and higher center of gravity (CG) at takeoff. The height of CG at touchdown, takeoff and calf angles, the distance from CG to heel, and maximal knee flexion during contact time among the athletes of various qualifications differ insignificant.